Psychological and Sensory Determinants of Fall Risk among Older Adults: A Cross-Sectional Analysis in Indonesian Long-Term Care Facilities - Lina Safarina; Dafariza Arkhabi; Novie E. Mauliku; Tria Firza Kumala (The Indonesian Institute of Science and Technology Research, 2026)
Falls represent a significant health issue among the elderly worldwide, particularly those residing in long-term care institutions. Although physical and environmental causes have been widely examined, there is limited research within Indonesian settings that investigates how psychological and sensory factors contribute to fall risk in institutionalized older adults. This study explores the association between psychological and sensory factors with the risk of falls among elderly individuals living in Indonesian care facilities. A cross-sectional analytical study was carried out involving 100 individuals aged 60 years and older in various long-term care homes across Indonesia. Data were obtained through structured interviews using standardized tools. Bivariate analyses were then analyzed using multivariable logistic regression to determine independent predictors. Out of all participants, 46% were found to have a heightened risk of falling. Multivariate analysis showed that higher levels of fear of falling (OR = 1.15; 95% CI: 1.04–1.28; p = 0.006), anxiety (OR = 2.97; p = 0.005), depression (OR = 2.85; p = 0.008), poor sleep quality (OR = 3.81; p = 0.001), visual problems (OR = 2.14; p = 0.038), hearing challenges (OR = 2.50; p = 0.022), and advancing age (OR = 1.04; p = 0.049) were all significantly linked to fall risk. This study highlights that psychological and sensory health significantly impact fall vulnerability among elderly residents in care institutions. Incorporating these often-overlooked dimensions into routine fall risk assessments may enhance preventative care approaches.